An Early Broad Competence of Motoneurons to Express ER81 Is Later Sculpted by the Periphery - Wang, Guoying (J Neurosci, 2004)
The ETS transcription factor ER81 is expressed in sensory neurons and motoneurons that innervate the adductor and femorotibialis muscles in chick hindlimb and is essential for the development of monosynaptic connections between these two populations of neurons. Neurons need a signal(s) from limb bud mesoderm to initiate ER81 expression. It is not known whether the mature expression pattern arises because adductor and femorotibialis motoneurons are uniquely competent to respond to peripheral signals and express ER81, or whether all motoneurons are competent to express ER81, but normally only adductor and femorotibialis motoneurons are exposed to the requisite activating signal. To investigate these possibilities, we examined ER81 expression in motoneurons that encountered limb tissue surgically mismatched with their target identity at stages after motor pool identities are established. We found that ER81 expression was not invariably linked to motor pool identity or target innervation and was more malleable in later-born femorotibialis motoneurons than in earlier-born adductor motoneurons. We also found that ER81 expression is regulated differently in sensory neurons and motoneurons. Most striking was the observation that motoneurons caudal to the normal adductor and femorotibialis pools could express ER81 when exposed to the appropriate peripheral signals, although this competence did not extend through the entire lumbosacral (LS) region. Thus, it appears that a prepattern of competence to express ER81 is established in early LS motoneurons, most likely in concert with their target identity, and that the expression domains of motoneurons are subsequently refined by peripheral signals at later stages.